The Influence of TLRHP on the Level of Government Compliance in LKPD Disclosures: a Study in Districts/Cities in Central Sulawesi Province - NANDA, Nanda; DIN, Muhammad; JURANA, Jurana; MUFIDAH, Andi Ainil (PT Keberlanjutan Strategis Indonesia, 2024)
The research aims to see the effect of follow-up recommendations from audit results on compliance in disclosing local government financial reports. Using a quantitative approach, the secondary data comes from the Ministry of Finance and BPK RI regarding follow-up to audit recommendations in 2018-2022. Data analysis was carried out using the PLS SEM method using WarpPLS 7.0. The research results show that follow-up to audit recommendations has a positive and significant effect on government compliance and strengthens the relationship in the disclosure of regional government financial reports, with path coefficients of 0.27 and 0.26, respectively. The R² value of 0.23 indicates that the two variables explain 23% of the variability in compliance levels. Model fit testing shows valid results, with all model indices meeting the fit criteria. The research results reveal that the Follow-up to Audit Result Recommendations (TLRHP) has a positive and significant influence on the Level of Compliance (TKPTHN) and strengthens the Disclosure of Regional Government Financial Reports (PLKPD). Implementation of audit recommendations and transparency of financial management is critical to increase regional government accountability. Although these variables explain 23% of the variation in compliance, other factors still contribute. This research suggests a qualitative approach for further studies to explore the relationship between audit and compliance and the impact of monitoring systems on corruption prevention.